2017
DOI: 10.1371/journal.pntd.0005162
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Impact of Intervention Strategies for Sleeping Sickness in Two High-Endemicity Health Zones of the Democratic Republic of Congo

Abstract: Two goals have been set for Gambian human African trypanosomiasis (HAT), the first is to achieve elimination as a public health problem in 90% of foci by 2020, and the second is to achieve zero transmission globally by 2030. It remains unclear if certain HAT hotspots could achieve elimination as a public health problem by 2020 and, of greater concern, it appears that current interventions to control HAT in these areas may not be sufficient to achieve zero transmission by 2030. A mathematical model of disease d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 36 publications
(59 reference statements)
2
73
0
Order By: Relevance
“…While active screening and treatment have been responsible for the majority of this decline, in the last decade, new cost-effective methods of controlling riverine species of tsetse-the important vectors of T. b. gambiense-have begun to make an important contribution to the global effort. In particular, 'Tiny Targets' are-despite their small size-proving highly effective in reducing the density of riverine species where active screening and treatment alone is not predicted to achieve the elimination goals [178,179]. Tiny Targets are currently deployed by control programmes in Chad, Côte d'Ivoire, the Democratic Republic of Congo, Guinea, and Uganda.…”
Section: Ntds-lagging Behind In Vector Controlmentioning
confidence: 99%
“…While active screening and treatment have been responsible for the majority of this decline, in the last decade, new cost-effective methods of controlling riverine species of tsetse-the important vectors of T. b. gambiense-have begun to make an important contribution to the global effort. In particular, 'Tiny Targets' are-despite their small size-proving highly effective in reducing the density of riverine species where active screening and treatment alone is not predicted to achieve the elimination goals [178,179]. Tiny Targets are currently deployed by control programmes in Chad, Côte d'Ivoire, the Democratic Republic of Congo, Guinea, and Uganda.…”
Section: Ntds-lagging Behind In Vector Controlmentioning
confidence: 99%
“…From the start of the NTD Modelling Consortium in 2015, there have been several other examples of impactful modelling, which could be divided over three major scales of operations: (1) developing WHO guidelines (e.g., for triple-drug therapy, with ivermectin, diethylcarbamazine, and albendazole, against lymphatic filariasis [16,17]); (2) informing funding decisions for new intervention tools (e.g., the development of a schistosomiasis vaccine [18]); and (3) guiding within-country targeting of control (e.g., local vector control for human African trypanosomiasis in the Democratic Republic of the Congo [19,20] and Chad [21]).…”
Section: Examples Of Successes In Modelling For Policy In the Field Omentioning
confidence: 99%
“…Behavioural studies have shown that this species is responsive to Tiny Targets [13]. Accordingly, we implemented a large-scale trial of Tiny Targets in Yasa Bonga Health Zone, one of the foci where the addition of vector control to screening activities is predicted to accelerate progress towards the elimination goal [4,6]. To assist in the design and monitoring of the tsetse control operation, we also conducted a large-scale entomological survey of G. f. quanzensis in Yasa Bonga and its neighbouring health zones of Masi Manimba and Mosango ( Figure 1) and used remotely-sensed data to produce a map of tsetse habitat suitability for this important vector, which guided the deployment of targets and allowed us to assess their impact.…”
Section: Introductionmentioning
confidence: 99%